SATISFAÇÃO DOS DOCENTES COM OS RESULTADOS OBTIDOS DAS AVALIAÇÕES DOS ESTUDANTES DO ENSINO A DISTÂNCIA NA UNIRSIDADE PÚNGUÈ (REMUNOM, 2023)
Assessment based on monitoring and guiding the performance of learners during the learning process has been the target of trainers both in face-to-face and distance learning courses. The study seeks to understand the teachers' position on the assessments made by distance learning students. To answer this question, a qualitative research was carried out involving 80 professors. For data collection, an interview was conducted with teachers involved in this teaching modality. Thus, this article aims to understand the level of satisfaction of teachers in relation to the results of different types of assessments applied to Distance Education (EAD) students at the Púnguè University. Specifically, identify the way teachers evaluate students in this modality, describe the evaluation process in distance learning and relate the level of satisfaction with the different types of evaluation applied to students in distance learning. The data of this research come from the analysis of the answers of the professors of UniPúnguè in the City of Chimoio. Eighty (80) teachers participated in this research. From the analysis of the results, it is concluded that most of the professors at the Púnguè University are not very satisfied with the results obtained by their students during the entire teaching and learning process. And to minimize this problem, it is suggested that the evaluations be carried out in person. Keywords: Distance education; Evaluation; Satisfaction levels; University students.